The role of Islamic religiosity in social influence, price sensitivity, and the impulsive buying relationship - Harimurti Wulandjani (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2026)
This study investigates the moderating effect of Islamic religiosity on the relationships among social influence, price sensitivity, and impulsive buying behavior among young consumers in Indonesia. Using a convenience sample of 223 respondents, the study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0 to test the hypothesized relationships. The results confirm that social influence positively affects price sensitivity, whereas price sensitivity negatively influences impulsive buying. The direct effect of social influence on impulsive buying was not significant, indicating that it operates indirectly through price sensitivity. Islamic religiosity acts as a significant moderator in both the social influence–price sensitivity and social influence–impulsive buying relationships, strengthening these positive effects. However, the moderating role of Islamic religiosity on the price sensitivity–impulsive buying relationship was not supported. Public interest statements This study extends the consumer behavior literature by integrating the Stimulus-Organism-Response Framework and Self-Control Theory to explain the mediating role of price sensitivity and the contingent role of Islamic religiosity in shaping young consumers' susceptibility to social influence and their subsequent purchasing patterns, an area previously underexplored in the Indonesian market.